Factors Affecting Purchase Intention of South East Asian (SEA) Young Adults towards Global Smartphone Brands - Zahid, Wahid; Dastane, Omkar (UI Scholars Hub, 2021)
The study aims to probe the effect of perceived price, perceived quality, brand awareness, and social influence on purchase intention of South East Asian (SEA) Young Adults towards global smartphone brands. This explanatory research uses quantitative empirical data collected from 200 SEA Young Adults studying in one of the public universities in Malaysia. Stratified random sampling is used while ensuring fair representation of SEA countries, viz., Singapore, Malaysia, Philippines, Thailand, Indonesia, Vietnam, and Cambodia. Correlation and regression analysis were carried out using SPSS 20.0. The study resulted in the finding that social influence has the highest level of linear relationship and so is the most influential factor among four. The findings provide guidelines to global smartphone brands for developing value proposition and better promotion mix for smartphones promotion.